2014
DOI: 10.1002/ajmg.b.32224
|View full text |Cite
|
Sign up to set email alerts
|

Communication, cognitive development and behavior in children with Cornelia de Lange Syndrome (CdLS): Preliminary results

Abstract: In this study, we present preliminary data on cognitive, behavioral and communication domains of individuals with Cornelia de Lange Syndrome (CdLS), collected through a specific protocol combining direct and indirect tools. Seventeen subjects with CdLS were assessed, 2.5- to 13.4-year-old. Cognitive level of the subjects differed from what previously described in literature, showing more patients with normal or borderline cognitive abilities. We found a relation between severe autistic behavior and comprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 15 publications
7
43
1
1
Order By: Relevance
“…Six studies reported the presence of mutations in one or more genes . Four of these studies stratified data by genetic cause for development and behaviour.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies reported the presence of mutations in one or more genes . Four of these studies stratified data by genetic cause for development and behaviour.…”
Section: Resultsmentioning
confidence: 99%
“…13,28 Six studies reported the presence of mutations in one or more genes. 3,5,[29][30][31][32] Four of these studies stratified data by genetic cause for development and behaviour. Nakanishi et al 3 reported Autism Diagnostic Interview-Revised (ADI-R) and Vineland Adaptive Behavior Scales (VABS) results for patients with an NIPBL mutation (n=22) and ADI-R results for patients with an SMC1A mutation (n=3).…”
Section: Resultsmentioning
confidence: 99%
“…To date 36 different SMC1A mutations (28 missense mutations, 1 splice-site mutation, and 7 in-frame deletions) have been reported in 54 unrelated patients, 11 of which belong to four families (9,35,48,(53)(54)(55)(56)(57)(58). Furthermore, a t(X;8)(p.11.2;q24.3) translocation and an approximately 8 kb intragenic deletion including exons [14][15][16] have been reported (59,60). SMC1A escapes X-inactivation partially and mutations are identified in both genders with a female:male ratio of 2.4:1 (56).…”
Section: Smc1amentioning
confidence: 99%
“…Mutations in the gene NIPBL have been reported as causing the most typical CdLS phenotype, evident in arched eyebrows and long eyelashes, ID ranging from profound to normal/borderline, self‐injurious behaviour (SIB) and autism characteristics (Bhuiyan et al., ). An atypical presentation of autism, repetitive and stereotypical behaviour, social withdrawal, anxiety and expressive‐receptive language discrepancy have often been described in individuals with CdLS (Ajmone et al., ; Moss, Howlin, Magiati, & Oliver, ; Moss, Richards, Nelson, & Oliver, ; Oliver, Arron, Sloneem, & Hall, ).…”
Section: Introductionmentioning
confidence: 99%